An Expansion resources analysis of English and Vietnamese political editorials in the light of Appraisal Theory - Nguyen , Thi Thu Hien; Huynh , Thi Thu Toan (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
The paper investigates the use of Expansion resources in the English and Vietnamese political editorials about North Korea by drawing on Appraisal Theory. Firstly, the paper provides a brief account of Appraisal Theory, especially Expansion and subtypes of Expansion, namely Entertain and Attribution. Then, it is about the data and the methods applied. The findings indicate that there exist the similarities and differences in the resources of realizing Expansion and in the ways the writers negotiate with readers by means of using these resources.